2016
DOI: 10.1007/s10439-016-1716-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Preserves Pulsatile Pulmonary Arterial Hemodynamics in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is caused by extensive pulmonary vascular remodeling that increases right ventricular (RV) afterload and leads to RV failure. PAH predominantly affects women; paradoxically, female PAH patients have better outcomes than men. The roles of estrogen in PAH remain controversial, which is referred to as “the estrogen paradox”. Here, we sought to determine the role of estrogen in pulsatile pulmonary arterial hemodynamic changes and its impact on RV functional adaption to PAH. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…This comprehensive approach enabled demonstration of progression to Cpc-PH from Ipc-PH post-MI. Moreover, from ex vivo pulmonary vascular pressure-flow dynamics, we demonstrated that Cpc-PH in this model is not characterized by a change in characteristic impedance (indicative of proximal arterial stiffening) in contrast to findings in small animal models of pulmonary arterial hypertension (PAH) (44,74). Interestingly, there was also no change in distensibility of the small pulmonary arterioles.…”
Section: Discussionmentioning
confidence: 55%
“…This comprehensive approach enabled demonstration of progression to Cpc-PH from Ipc-PH post-MI. Moreover, from ex vivo pulmonary vascular pressure-flow dynamics, we demonstrated that Cpc-PH in this model is not characterized by a change in characteristic impedance (indicative of proximal arterial stiffening) in contrast to findings in small animal models of pulmonary arterial hypertension (PAH) (44,74). Interestingly, there was also no change in distensibility of the small pulmonary arterioles.…”
Section: Discussionmentioning
confidence: 55%
“…Pulmonary vascular resistance was increased twofold and pulmonary artery compliance (CPA) was decreased to 70% of control levels ( Table 2 ) to match experimental observations of increased PVR in mice following Bleo exposure ( Table 1 ; Hemnes et al, 2008 ) and experimental observations of decreased CPA in mice with other forms of PH ( Tewari et al, 2013 ; Liu et al, 2015 , 2017a ; Wang et al, 2018 ). Simulation of these changes in PVR and CPA resulted in elevations of right ventricular systolic pressure (RVSP) and arterial elastance (E a ) that were similar to experimental findings ( Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 72%
“…While Hemnes et al (2008) didn’t report pulmonary artery compliance (CPA), it is well known that as PVR increases in PH, CPA decreases ( Lankhaar et al, 2006 , 2008 ; Saouti et al, 2009 ) and this loss of compliance is an important component of RV afterload ( Wang and Chesler, 2013 ). Given this lack of data, decreases in CPA in response to Bleo were chosen to match published experimental measurements of CPA in mice with other forms of PH ( Tewari et al, 2013 ; Liu et al, 2015 , 2017a ; Wang et al, 2018 ). RV mass was increased to match RV hypertrophy reported by Cowley et al (2017) in Bleo mice.…”
Section: Methodsmentioning
confidence: 99%
“…More critically, E2 supplementation was associated with a significant reduction in postexercise total pulmonary resistance (a surrogate for PVR (203)), indicating superior performance of the E2-supplemented pulmonary vasculature after strenuous exercise. Liu et al examined the effect of E2 supplementation on pulmonary hemodynamics in ovariectomized females in the SuHx-PH mouse model and found that E2 decreased PA elastance (a marker of RV afterload) and increased PA global compliance and transpulmonary vascular efficiency (defined as the ratio of cardiac output to total hydraulic power over the cardiac cycle) (232,234,235). Structurally, the authors demonstrated that E2 supplementation rescued SuHx-induced increases in PA wall thickness and collagen content.…”
Section: Animal Studies Demonstrating Protective Estrogen Effects In mentioning
confidence: 99%
“…In summary, animal studies examining estrogen signaling in the pulmonary vasculature during PH have produced conflicting and paradoxical results ( Table 5). Exogenous E2 administration improves PH outcomes and limits pulmonary vascular remodeling in HPH (92,115,208,296,335,474), MCT-PH (99,432,483), and SuHx-PH (114,213,232,234). On the other hand, attenuation of estrogen signaling by aromatase inhibition or ER antagonists appears to be protective in the HPH, SuHx-PH, and BMPR2 mutation models of disease in female rodents (248).…”
Section: Animal Studies Identifying Estrogen As a Disease Mediator Inmentioning
confidence: 99%